Software Quality. - Denning, Peter J. (Communications of the ACM, 2016)
The article explores software quality as of 2016. Particular focus is given to the goals of software developers including dependability, reliability, usability, safety and security. Topics discussed by the author include the demands of software users, markets for software in the forms of apps (computer applications and the operating systems for the iPhone and Android cellular phones.